Analisis Strategi Perluasan Merek Menâs Biore - , Yance Somantri ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objevtive of this research is to analyze the success of Menâs Biore brand extension into a new category. The new selected categories are shampoo, hair style or cologne. The determining variables are category similarity, brand reputation, perception of risk whether its choice or consequences and consumer innovativeness. The collected data was driven from 300 respondents spread through Jakarta and greater Jakarta. Data collection method was direct interview with respondent that has fulfilled the required criteria. The result shows that variable category similarity and brand reputation are the keys to creating a success brand extension. Whereas brand extention created based on category similarity and has good brand reputation is likely to succeed.